Evaluation of Power Quality of Wind Turbines for AL Maqrun city in Libya - Albohli, Nafaa; Elosta, Wedad (IJRDO-Journal of Applied Science, 2016)
RACT The operation of wind turbines has an impact on the power quality of the electrical grid. The term power quality refers to voltage stability, frequency stability, and the absence of various forms of electrical noise (e.g., flicker and harmonic distortion) on the electrical grid. The power quality will vary from location to location, depending on the nature of the wind resource, the turbine/generator technology used, and the condition of the local electrical grid. The power will fluctuate due to wind speed variations. Power fluctuation is affected by the number of wind turbines and power control technology (pitch and stall regulation). It is important to study power fluctuations in order to reduce these fluctuations that could affect electrical networks, and therefore to choose a proper wind turbine. Power fluctuations from wind turbine generators can be predicted using two methodologies. The first method is the turbulence intensity in the power output of wind turbines, and the second method uses statistical data to analyze power output of wind turbines. In this paper the above mentioned parameters are studied through a statistical model using the above two methodologies. Wind data for AL Maqrun city in Libya was used for the analysis. This data was of ten minutes average for the year 2003. The results show that using two wind turbines instead of one turbine will improve the power quality. Similar results are noticed for pitch controlled against stall controlled. The results were compared with results available in the literature showing a good agreement.